Enzymatic upgrade of old paperboard containers - Pala, Helena (2009)
The use of enzymes in secondary fiber (old paperboard containers) upgrading was investigated. The following aspects were analyzed: (i) the effect of several enzymes and (non-hydrolytic) cellulose-binding domains on the pulp and paper properties; (ii) factors influencing enzymatic treatment of secondary fiber: enzyme dosage and reaction time; and (iii) enzyme action on fractions with different fiber-length. In general, all the tested enzymatic preparations were able to improve the pulp drainability. In most cases this improvement was obtained at the expense of paper strength. The use of cellulose-binding domains allowed for the simultaneous increase in drainability and strength properties.